Pengaruh Brand Image Dan Harga Terhadap Keputusan Pembelian Sepeda Motor Honda Scoopy Dengan Minat Beli Sebagai Variabel Intervening - Narendra Bagaskara, Nicodemus; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2021)
Abstract: The more motorcycle brands that are on the market, will lead costumer to have a greater opportunity to choose which products that suit them the most, which makes companies also have to improve ways such as increasing brand image and providing prices that can compete in the market. This study aims to determine the effect of brand image, price on purchasing decisions through purchase intention as an intervening variable for Honda Scoopy motorcycle products in the city of Semarang. This type of research is explanatory research and sampling using nonprobability sampling techniques, purposive sampling method. Data collection using questionnaires and google form. The sample used is 100 respondents of Scoopy consumers in Semarang City. This study uses quantitative and qualitative analysis with validity, reliability, correlation coefficient, determination coefficient, simple and multiple regression, significance t-test, f test, mediation test, and Sobel test. The results showed that brand image affected purchase intention, price affected purchase intention, brand image and price affected purchase intention. Then the brand image affects the purchase decision, the price affects the purchase decision, the purchase intention affects the purchase decision, there is an influence of the brand image on the purchase decision through the purchase intention, and there is a price effect on the purchase decision through the purchase intention. Keywords: Brand Image; Price; Purchase Decision; Purchase Intention Abstrak: Semakin banyak merek sepeda motor yang berada di pasaran, tentu akan membantu konsumen untuk memiliki kesempatan yang lebih besar untuk memilih produkmana yang dinginkan dan dibutuhkan, yang menjadikan perusahaan juga harus meningkatkan cara seperti meningkatkan brand image dan memberikan harga yang dapat bersaing dipasaran. Penelitian ini bertujuan untuk mengetahui pengaruh brand image, harga terhadap keputusan pembelian melalui minat beli sebagai variable intervening produk sepeda motor honda scoopy di kota Semarang. Tipe penelitian adalah explanatory research dan pengambilan sample menggunakan teknik nonprobability sampling, metode purposive sampling. Pengumpulan data menggunakan kuesioner dan google form. Sampel yang digunakan sebanyak 100 responden konsumen Scoopy di Kota Semarang. Penelitian ini menggunakan analisis kuantitatif dan kualitatif dengan uji validitas, reliabilitas, koefisien korelasi, koefisien determinasi, regresi sederhana dan berganda, signifikasi uji t, uji F, uji mediasi, dan uji sobel.Kata kunci: Brand Image; Harga; keputusan pembelian; niat membeli